Tarantulas and social spiders : a tale of sex and silk - Bull, Jonathan (2012)
Studies of spider silks indicate that they may outperform virtually all synthetic fibres in terms of strength, elasticity and toughness. To date, most silks studied come from only a select few species and likely underrepresent the immense diversity of the clades. Here, protein and mRNA sequence analyses were used to study silk from two types of spider. The first approach used ESI tandem mass spectrometry to sequence peptide fragments of a silk from a tarantula (Mygalomorphae, Theraphosidae), a hitherto neglected family. The results confirm that the common silk types found in araneomorph spiders, Spidroin 1 and Spidroin 2, are also found in mygalomorphs. A putative N-terminal domain that bears a striking similarity to the N-terminus of araneomorph pyriform silk was isolated. If correctly identified, this would be the first ever recorded N-terminal domain for a mygalomorph. The second approach taken was to construct a cDNA library from theraphosid silk glands and adjacent tissue. Sequencing identified a significant number of uniquely truncated rRNAs. These may be the result of specific 'fragile sites' within these transcripts, which would explain the discrete classes of length polymorphisms found. The cDNA library sequences also provided evidence consistent with RNA editing and furthermore identified the presence of both transcribed nuclear pseudogenes and transposable elements. These may reflect past evolutionary horizontal gene transfer events within the spider genome. Similar analysis of next generation sequencing data from the transcriptomes of three Stegodyphus spp. (Araneomorphae) reveal a range of apparent silk types with similarity to major ampullate, minor ampullate and pyriform silks. These were identified by searching for comparative sequence homologies using Microsoft Office Word. No flagelliform silk or recognisable sticky silks were identified, which is consistent with the biology of Stegodyphus species. In addition to studies of silk, previous common conceptions of dimensional morphologies were examined to see if they could adequately sex theraphosid spiders, including the species that was the subject of the silk study already described. An independent samples t-test was conducted to compare morphologies of particular leg hairs and statistical analysis demonstrated that there were significant differences between males and females (t (70) = 9.445, p < .001). This technique may be important in future evolutionary and ecological studies of theraphosids.